2021
DOI: 10.1016/j.sjbs.2021.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin prevents myocardial infarction adverse remodeling in rats by attenuating TGF-β1/Smad3 signaling: Different mechanisms of action

Abstract: This study investigated the anti-remodeling and anti-fibrotic and effect of quercetin (QUR) in the remote non-infarcted of rats after myocardial infarction (MI). Rats were divided as control, control + QUR, MI, and MI + QUR. MI was introduced to the rats by ligating the eft anterior descending (LAD) coronary artery. All treatments were given for 30 days, daily. QUR persevered the LV hemodynamic parameters and prevented remote myocardium damage and fibrosis. Also, QUR supressed the generation of ROS, increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…Among these bioactive components (Figure 3), some were dedicated to pain relief or cancer treatment (Gao et al, 1994;Xu et al, 2012;Chen et al, 2016;Wang et al, 2016;Wang et al, 2019), while berberine, coptisine, THP, palmatine, and quercetin were reported to be cardioprotective (Kim et al, 2009;Guo et al, 2013;Zhu et al, 2020;Albadrani et al, 2021). In this study, we conducted molecular docking of the 5 components with AKT1, the core target related to the PI3K/Akt pathway.…”
Section: Results Of Molecular Docking Analysismentioning
confidence: 99%
“…Among these bioactive components (Figure 3), some were dedicated to pain relief or cancer treatment (Gao et al, 1994;Xu et al, 2012;Chen et al, 2016;Wang et al, 2016;Wang et al, 2019), while berberine, coptisine, THP, palmatine, and quercetin were reported to be cardioprotective (Kim et al, 2009;Guo et al, 2013;Zhu et al, 2020;Albadrani et al, 2021). In this study, we conducted molecular docking of the 5 components with AKT1, the core target related to the PI3K/Akt pathway.…”
Section: Results Of Molecular Docking Analysismentioning
confidence: 99%
“…Quercetin has been reported to have protective effects on the heart because of its antioxidant, anti-inflammatory, and other biological properties ( 35 ). Albadrani et al revealed that quercetin upregulates Smad7 and has an anti-fibrosis effect ( 36 ). Quercetin is contained in TSF herbs, such as rhubarb root and rhizome, notoginseng root, cornus fruit, burning bush twig, and astragalus root, so the TSF regulation of Smad7 is dependent on quercetin.…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin has a significant therapeutic effect on ventricular remodeling model rats after AMI, which is mainly reflected by reducing myocardial injury and myocardial fibrosis, inhibiting the production of ROS, increasing the levels of SOD and GSH, and reducing NF‐κB. The mechanism is related to its scavenging ROS and inhibiting the NF‐κB signaling pathway (Albadrani et al, 2021). Pretreatment with quercetin could reduce the infarct size, improve the left ventricular (LV) functions, and reduce circulatory levels of lactate dehydrogenase (LDH) and creatinine‐kinase MB (CKMB) in AMI rats.…”
Section: Introductionmentioning
confidence: 99%